Public health concerns arising from interventions designed to circumvent polluted surface drinking water in Shenqiu County, Henan, China. (December 2017) - Qu, Weidong; Zheng, Weiwei; Spencer, Peter; Zheng, Jianheng; Yang, Lan; Han, Fengchan; Yan, Liyun; Ma, Wuren; Zhou, Ying; Zheng, Yuxin; Wang, Youfa
Abstract: Background: Successful intervention programmes to address environmental pollution are important. High cancer mortality associated with manmade chemical pollution of drinking water has been reported in Shenqiu County, Henan, China. Deep wells have been introduced to obtain non-polluted drinking water, which might contain natural contaminants. We investigated fluoride and arsenic concentrations in deep-well water (intervention areas) versus shallow water (non-intervention areas), and compared corresponding rates of dental fluorosis in children. Methods: Water samples (n=130) were collected in Sept 16–21, 2013, from rivers, shallow wells, and deep wells in Shenqiu County. We measured fluoride with an ion-selective electrode (US Environmental Protection Agency method), and arsenic levels were determined by inductively coupled plasma mass spectrometry. Dental fluorosis according to the National Standard for Diagnosis of Dental Fluorosis (WS/T 208-2011; the national diagnostic standard for dental fluorosis in China) was scored for students in rural elementary schools (280 students, 140 in deep water areas, 140 in shallow water areas). Group differences were assessed using Student's t test. The study was approved by the Institutional Review Board the of School of Public Health, Fudan University (IRB00002408, FWA00002399; approval number IRB#2013-03-0418). All students and their parents gave written informed consent. Findings: Concentrations of fluoride (range 1·2–2·8 mg/L) and arsenic (15–26 μg/L) in deep wells were up to three times higher than concentrations in shallow wells (fluoride 0·3–0·8 mg/L, p=0·006; arsenic 3–8 μg/L, p=0·002) or surface water (fluoride 0·2–0·6 mg/L, p=0·0008; arsenic 1–5 μg/L, p=0·007). Concentrations in surface water and shallow-well water were similar (p=0·525 for fluoride; p=0·236 for arsenic). 18 (13%) students exposed to deep water had dental fluorosis, compared with no students using shallow-well water. In deep-well water, arsenic concentration exceeded by two to three times the US maximum contaminant level of 10 μg/L, although fluoride was below the maximum contaminant level of 4 mg/L. Interpretation: Government-funded deep wells have aimed to address health problems related to water pollution in Shenqiu, China, but have led to increased dental fluorosis in children. Research and governments need to investigate the potential unintended consequences of government-sponsored programmes to address environmental pollution. Funding: Chinese National Natural Science Foundation (81325017, 81630088); High-Technology R&D 863 Program of the Chinese Ministry of Science and Technology (2013AA065204).